General and Special Education Teachers’ Attitudes Toward Co- Teaching in an Inclusive Private Setting in Dubai - Obeidat, Walid (2020)
This research investigates general and special education teachers' attitudes towards co-teaching. Includes investigating their attitudes towards the co-teaching model and the impact of collaboration, personal skills, and teachers' characteristics on co-teaching implementation. The study will provide important information about the difficulties facing educators in implementing effective co-teaching. The data obtained from this research will help understand general and special teachers' attitudes towards co-teaching, its efficiency, and the barriers it faces in its implementation. Moreover, help the schools create a more effective support system of inclusive education for all learners in the future. The study targeted general education and special education teachers working in inclusive classrooms from the KG stage to grade 12 in a private school in Dubai. The data collected by individual surveys and semi-structured interviews indicated that the general and special education teachers have a positive attitude toward co-teaching. Further, lack of professional development, lack of time allocated for planning, lack of human and educational resources has been identified as the barriers facing the effective implementation of co-teaching.